Functional foods, nutraceuticals, and degenerative disease prevention - Paliyath, Gopinadhan; Bakovic, Marica; Shetty, Kalidas (Chichester, West Sussex, UK ; Ames, Iowa : Wiley-Blackwell, 2011)
"Functional Foods, Nutraceuticals and Degenerative Disease Prevention is a compilation of different segments of functional foods and nutraceuticals focusing on their mechanism of action in the human body leading to disease prevention. Numerous chapters deal with different functional foods in terms of their efficacy, highlighting the mechanism of action of their ingredients. The book focuses on the biochemistry and molecular biology of the disease prevention process rather than simply compiling the benefits of functional foods and nutraceuticals."--
Front Matter -- Functional Foods, Nutraceuticals, and Disease Prevention: A Window to the Future of Health Promotion / Gopinadhan Paliyath, Kalidas Shetty -- Functional Foods and Nutraceuticals / Chung-Ja C Jackson, Gopinadhan Paliyath -- Nutritional Genomics: Fundamental Role of Diet in Chronic Disease Prevention and Control / Amy J Tucker, Branden Deschambault, Marica Bakovic -- Nutraceuticals and Antioxidant Function / Denise Young, Rong Tsao, Yoshinori Mine -- Composition and Chemistry of Functional Foods and Nutraceuticals: Influence on Bioaccessibility and Bioavailability / Jissy K Jacob, Gopinadhan Paliyath -- Cruciferous Vegetable-Derived Isothiocyanates and Cancer Prevention / Ravi P Sahu, Sanjay K Srivastava -- The Disease-Preventive Potential of Some Popular and Underutilized Seeds / Rajeev Bhat -- Effects of Carotenoids and Retinoids on Immune-Mediated Chronic Inflammation in Inflammatory Bowel Disease / Hua Zhang, Ming Fan, Gopinadhan Paliyath -- Ruminant Fat as Potential Nutraceutical Components to Prevent Cancer and Cardiovascular Disease / Ye Wang, Catherine J Field, Spencer D Proctor -- Nanotechnology for Cerebral Delivery of Nutraceuticals for the Treatment of Neurodegenerative Diseases / Jasjeet Kaur Sahni, Sihem Doggui, Ľ Dao, Charles Ramassamy -- Cancer Prevention by Polyphenols: Influence on Signal Transduction and Gene Expression / Fatima Hakimuddin, Gopinadhan Paliyath -- PotatoHerb Synergies as Food Designs for Hyperglycemia and Hypertension Management / Fahad Saleem, Ali Hussein Eid, Kalidas Shetty -- Fermentation-Based Processing of Food Botanicals for Mobilization of Phenolic Phytochemicals for Type 2 Diabetes Management / Chandrakant Ankolekar, Kalidas Shetty -- Postharvest Strategies to Enhance Bioactive Ingredients for Type 2 Diabetes Management and Heart Health / Dipayan Sarkar, Kalidas Shetty -- Enhancing Functional Food Ingredients in Fruits and Vegetables / Shaila Wadud, Gopinadhan Paliyath -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Functional foods; Degeneration (Pathology) -- Prevention; Medicine, Preventive; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Degeneration (Pathology) -- Prevention; Functional foods; Medicine, Preventive; Electronic books